Frameworks for Tourism Research - Pearce, Douglas (CABI, 2014)
Much of the research for this book was undertaken during periods of research and study leave from Victoria University of Wellington. Part of this leave was spent in the School of Travel Industry Management at the University of Hawaii, Manoa, where I was hosted by Pauline Sheldon and Gui Lohmann. Fruitful discussions about frameworks were had with Adam Weaver, who also read and provided insightful feedback on parts of the text. Heike Schanzel provided valuable bibliographic assistance and carefully prepared the manu- script while Tibor Zsirmik drew or redrew a number of the figures. Chantal's continuing support has enabled the successful completion of the manuscript.